Global climate change: wild fires and permafrost degradation in the Republic of Buryatia (Eastern Siberia, Russia) - Badmaev, Nimazhap; Bazarov, Aleksandr; Kulikov, Anatoly; Gyninova, Ayur; Sympilova, Darima; Shakhmatova, Ekaterina; Badmaeva, Natalya; Gonchikov, Bato-Munko; Mangataev, Aleksandr (IOP Conference Series: Earth and Environmental Science, 2019)
Abstract On the territory of the Republic of Buryatia due to global climate change, significant transformations of the natural environment have been observed. Statistically significant trends of increase in temperature and decrease in precipitation with identification of wet and dry periods have been established. In the last 20 years due to the abnormally high air temperatures and the increasing aridity of the territory, the frequency and area of fires have increased, the rate of permafrost degradation on the southern boundary of the permafrost zone in the soils of meadow-steppe landscapes has increased twice.